Analysis Of Mathematics Books In The Basic Education Stage According To TIMSS Standards (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current research aims to identify the inclusion of international tests standards TIMSS-2015 in mathematics books for the basic education stage of the fourth primary (basic) and intermediate second (eighth basic) grades in the Republic of Iraq. The researcher used the descriptive and analytical approach in the content analysis method. The content of mathematics books scheduled for the basic education stage the research tools were cards for content analysis and to determine the extent to which the research objectives were achieved, a preliminary list of TIMSS-2015 standards was adopted, which was adopted in the study (Tabaza, 2018). (The basic eighth) in its two parts (the first and second), and a sample of the analysis sample was presented to a number of arbitrators, and it was agreed on the validity of the paragraphs and to ensure the consistency of the analysis in two ways, the first is the researcher with himself and the second the researcher with other analysts after a specific period of time has passed and I got an agreement that ranges from Between (88% - 97%), as the data and ratios were processed in stability using the Holsti equation, and the results were reached, there is agreement in most of the criteria, because all irrigation books Notes were prepared according to TIMSS-22015 standards, according to these results a number of recommendations were made, including: Taking the results and employing them in developing mathematics books to rise with the content of mathematics books in other developed countries according to the international tests TIMSS-2015. Mathematics in basic education stages in light of the requirements of international studies TIMSS-2015.